Instilling Character Education in Early Childhood by Using Illustrated Storybook - Retnaningrum, Wulandari (International Conference of Moslem Society, 2019)
Early childhood is in its golden age and is very valuable compared to later ages. Early childhood experiences a very rapid process of growth and development. The intelligence of early childhood develops tremendously in absorbing everything in the surrounding environment. The golden age is a very decisive initial foundation in shaping the character and commendable personality and will adhere to adult children. Character education with an Islamic perspective will give birth to future generations who have quality personalities for the future of their lives in the future. Instilling character education in schools has an important role and spearheads the teacher. Character education is very appropriate to be implemented early. Early childhood does not know yet, has not been able to distinguish and does not yet know the effects of good deeds and bad deeds that they do. Educators should build the character of early childhood by introducing a variety of goodness, familiarizing and instilling pleasure to do good deeds. Learning method that can be applied to instill character from early childhood is through storytelling methods using illustrated storybook. Illustrated storybook is very interesting for early childhood because children can see various things and can develop imagination or fantasy, train emotions, attention and build the character of the child so that the Indonesian people have a future generation with good character.